PERAN MODAL MANUSIA DAN MODAL INVESTASI TERHADAP NILAI PRODUKSI INDUSTRI KECIL DI KOTA PEKANBARU - Rahman, Fatkhurahman (Jurnal Benefita, 2017)
Performance management is a thriving little industry is currently in Pekanbaru related to the weakening of production and market production is still not able to show an encouraging movement when compared to a large industrial sector. While little is known industry was resilient to the crisis of higher and this needs to be addressed. This study uses secondary data and analyzed using SPSS. Based on the study results proved that human capital factors and factors of investing their capital together a significant effect on the value of production. However, partially / singly only human capital Â factors alone that influence significantly, amounting to 0,000. Also note that the purchasing power factor contributing positively to the production of small industries.